Meningkatkan Pemahaman Orangtua dalam Memilih PAUD yang Tepat Untuk Masa Depan Anak di PAUD Widya Kharisma - Rina Insani Setyowati; Dessy Farantika; Yuni Anisa (Civiliza Publishing, 2026)
(1) Background: Children’s school readiness is a key factor influencing their academic and social success. The transition from Early Childhood Education (ECE) to primary school often presents challenges that may lead to anxiety and adjustment difficulties if not properly supported by parents and ECE institutions. (2) Purpose: This study aimed to strengthen the involvement of parents and ECE units in preparing children for a positive and low-stress transition to primary education. (3) Methods: The activity was conducted on September 06, 2025, using interactive dialogue, lectures, group discussions, and question-and-answer sessions. (4) Results: The socialization activity enhanced parents’ and educators’ understanding of the importance of selecting quality ECE institutions and supporting children’s readiness for future learning. (5) Conclusions: Awareness-building efforts for parents of PAUD Widya Kharisam and ECE educators contribute to improving children’s social, emotional, and academic competencies required for successful adaptation to primary school.